Peculiarities of detecting small-size unmanned aerial vehicles using the radioacoustic location method - Oleinikov, V.M. (Radiotekhnika, 2025)
The article states that modern technical means for detecting low-observable small-sized unmanned aerial vehicles (sUAVs) in some cases do not provide adequate responsiveness and reliability. One of the promising directions for improving the efficiency of detecting low-observable sUAVs is the use of electromagnetic wave scattering on acoustic disturbances generated by these vehicles in the surrounding air environment. The article examines the characteristics of the acoustic field of sUAVs. Acoustic radiation from sUAVs has a number of specific features that must be considered when developing a radio-acoustic location system. The acoustic emission spectrum of sUAVs contains harmonics of the rotor rotation frequency and blade-passing frequency. Its spatial directivity is complex and, during maneuvering, affects both the intensity and shape of the acoustic signal spectrum. The operating frequency band of the location system should cover the range in which effective resonant scattering of electromagnetic waves is ensured. To reduce the size of highly directional antennas, the radar frequency is selected in such a way that the Bragg conditions are satisfied using higher-order diffraction. When receiving a signal scattered on inhomogeneities caused by the acoustic emission of sUAVs, the signal at the receiver input is the result of the interference of electromagnetic waves reflected from acoustic waves moving in opposite directions. The parameters of the envelope of this signal depend on the speed of sound, the frequency of the acoustic emission, and the ratio of the powers of signals formed in the sections before and after the sUAV within the antenna’s radiation pattern. The method of simulation modeling was used to study the features of higher-order diffraction of electromagnetic waves on the acoustic emission of sUAVs. It was found that the main part of the energy of the scattered signal is formed by acoustic oscillations in the immediate vicinity of the sUAV, whereas the contribution of oscillations at longer distances is negligible due to their attenuation. Maximum values of the reflection coefficient are achieved only when using antennas with a beamwidth of less than 4–6°, which provides spatial selection of the wavefront segments of the acoustic emission that enable coherent summation of the scattered signals. Deviation of the radar antenna from the direction toward the sUAV disrupts the conditions for coherent summation of the scattered signals from the wavefronts of the sUAV’s acoustic field.